Toroidal and magnetic Fano resonances in planar THz metamaterials - Srivastava, Yogesh Kumar (2017)
The toroidal dipole moment, a localized electromagnetic excitation of torus magnetic fields, has been observed experimentally in metamaterials. However, the metamaterial based toroidal moment was restricted at higher frequencies by the complex three-dimensional structure. Recently, it has been shown that toroidal moment could also be excited in a planar metamaterial structure. Here, we use asymmetric Fano resonators to illustrate theoretically and experimentally the underlying physics of the toroidal coupling in an array of planar metamaterials. It is observed that the anti-parallel magnetic moment configuration shows toroidal excitation with higher quality (Q) factor Fano resonance, while the parallel magnetic moment shows relatively lower Q factor resonance. Moreover, the electric and toroidal dipole interferes destructively to give rise to an anapole excitation. The magnetic dipole-dipole interaction is employed to understand the differences between the toroidal and magnetic Fano resonances. We further study the impact of intra unit-cell coupling between the Fano resonator pairs in the mirrored and non-mirrored arrangements. The numerical and theoretical approach for modelling the near-field effects and experimental demonstration of toroidal and magnetic Fano resonances in planar systems are particularly promising for tailoring the loss in metamaterials across a broad range of the electromagnetic spectrum.